Design and Construction of Vibrio cholerae Strains That Harbor Various CTX Prophage Arrays - Yu, Hyun J.; Cha, Da S. R.; Shin, Dong-Hun; Nair, Gopinath B.; Kim, Eun J.; Kim, Dong W. (Frontiers in Microbiology, 2018)
Toxigenic Vibrio cholerae strains arise upon infection and integration of the lysogenic cholera toxin phage, the CTX phage, into bacterial chromosomes. The V. cholerae serogroup O1 strains identified to date can be broadly categorized into three main groups: the classical biotype strains, which harbor CTX-cla; the prototype El Tor strains (Wave 1 strains), which harbor CTX-1; and the atypical El Tor strains, which harbor CTX-2 (Wave 2 strains) or CTX-3~6 (Wave 3 strains). The efficiencies of replication and transmission of CTX phages are similar, suggesting the possibility of existence of more diverse bacterial strains harboring various CTX phages and their arrays in nature. In this study, a set of V. cholerae strains was constructed by the chromosomal integration of CTX phages into strains that already harbored CTX phages or those that did not harbor any CTX phage or RS1 element. Strains containing repeats of the same kind of CTX phage, strains containing the same kind of CTX phage in each chromosome, strains containing alternative CTX phages in one chromosome, or containing different CTX phages in each chromosome have been constructed. Thus, strains with any CTX array can be designed and constructed. Moreover, the strains described in this study contained the toxT-139F allele, which enhances the expression of TcpA and cholera toxin. These characteristics are considered to be important for cholera vaccine development. Once their capacity to provoke immunity in human against V. cholerae infection is evaluated, some of the generated strains could be developed further to yield cholera vaccine strains.